Effect of different vitamin D3 metabolites on intestinal calcium homeostasisrelated gene expression in broiler chickens - Hsiao, Felix Shih-Hsiang; Cheng, Yeong-Hsiang; Han, Jin-Cheng; Chang, Ming-Huang; Yu, Yu-Hsiang (Brazilian Journal of Animal Science, 2018)
The purpose of this study was to investigate the effects of vitamin D3 metabolites 1α-hydroxycholecalciferol (1α(OH)D3 ), 25-hydroxycholecalciferol (25(OH)2 D3 ), and 1,25-dihydroxycholecalciferol (1,25(OH)2 D3 ) on growth performance, bone quality, and intestinal calcium homeostasis-related gene expression in broiler chickens. One-day-old broilers were fed a basal diet and basal diet containing different vitamin D3 metabolites. The body weight, feed intake, and feed conversion ratio in control and experimental broilers were measured to assess the growth performance, mineral levels, and bone breaking strength. The duodenum was used to assess calcium homeostasis-related gene expressions by quantitative reverse transcription-PCR. No statistically significant difference was found in growth performance, mineral deposition, or bone breaking strength in broiler chickens after three weeks feeding with vitamin D3 . However, supplementation of vitamin D3 metabolites tended to improve feed conversion rate, bone mineral deposition, and breaking strength in broiler chickens. The results demonstrated that vitamin D3 metabolites significantly upregulated calcium homeostasis-related genes, including calbindin, β-glucuronidase, TRPV6, and Na/Pi IIb cotransporter, mRNA levels after 12 h of feeding. The vitamin D3 metabolite 1,25(OH)2 D3 was the most effective at regulating calcium homeostasis-associated gene expression after 6 h of feeding. Dietary vitamin D3 metabolites may alleviate the development of TD in broiler chickens and these effects probably occur through regulation of intestinal calcium homeostasis-related gene expression
Keywords: gene; 1α-hydroxycholecalciferol; 25-hydroxycholecalciferol; 25-hydroxycholecalciferol